2008
DOI: 10.1002/chir.20672
|View full text |Cite
|
Sign up to set email alerts
|

Potential of different techniques of preferential crystallization for enantioseparation of racemic compound forming systems

Abstract: Recently the feasibility of preferential crystallization for enantioseparation of racemic compound forming systems has been demonstrated (Lorenz et al., Application of preferential crystallization to resolve racemic compounds in a hybrid process. Chirality 2006;18:828-840; Polenske et al., Separation of the propranolol hydrochloride enantiomers by preferential crystallization: thermodynamic basis and experimental verification. Cryst Growth Des 2007;7:1628-1634). Here, the development and the potential of an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 17 publications
1
35
0
5
Order By: Relevance
“…In this case, preferential crystallization can be applied, which was recently verified to be a promising process to separate not only compound-forming systems but also conglomerates. 21,22,24,25 In case of compound-forming systems, the racemate contains equal amounts of enantiomers arranged in an alternating pattern in the unit cell. 12 Pure enantiomer can be obtained from an enriched supersaturated solution by seeding with the same enantiomer.…”
Section: The Novel Hybrid Two-step Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, preferential crystallization can be applied, which was recently verified to be a promising process to separate not only compound-forming systems but also conglomerates. 21,22,24,25 In case of compound-forming systems, the racemate contains equal amounts of enantiomers arranged in an alternating pattern in the unit cell. 12 Pure enantiomer can be obtained from an enriched supersaturated solution by seeding with the same enantiomer.…”
Section: The Novel Hybrid Two-step Processmentioning
confidence: 99%
“…Thus, for the production of pure target enantiomer, the degree of undercooling should not exceed the metastable zone width of racemic compound to avoid the nucleation of the counter species. 24 If the process is stopped at point P 2 , pure enantiomer can be obtained as the product of the described hybrid process. c. The solution is just slightly enriched (e.g., M 3 ) and removal of solvent leads to a point in the three-phase region (I 3 ).…”
Section: The Novel Hybrid Two-step Processmentioning
confidence: 99%
“…[111,113] 2) Wie in Abbildung 3 b durch den schwarzen Punkt angedeutet, kann in einem ersten Schritt auch eine Enantiomerenanreicherung über die flüssige Phase erzielt werden. Hierbei genügt bereits eine geringe Asymmetrie in der enantiomeren Zusammensetzung, um eine flüssige Phase zu erhalten, aus der unter bestimmten Bedingungen die selektive Kristallisation eines reinen Enantiomers mçglich ist.…”
Section: Angewandte Chemieunclassified
“…In 2012, it was demonstrated that one of the nonsteroidal anti-inflammatory drugs, ketoprofen, if it is nearly racemic (1.2% ee), then it can be spontaneously resolved into two enantiomers by a simple crystallization under nonequilibrium preferential enrichment conditions (Figure 1.41). 90 Another form of a direct crystallization is a preferential crystallization, 91,92 which is also called resolution by entrainment of one enantiomer. [93][94][95] The process involves solution formation, e.g., under elevated temperature that will then be subcooled and seeded with crystals of the preferred species.…”
Section: Spontaneous Resolution and Preferential Crystallizationmentioning
confidence: 99%
“…90 Another form of a direct crystallization is a preferential crystallization, 91,92 which is also called resolution by entrainment of one enantiomer. [93][94][95] The process involves solution formation, e.g., under elevated temperature that will then be subcooled and seeded with crystals of the preferred species. Preferential crystallization is a potent method for the improvement of the product quality and at the same time achievement of a higher yield and productivity.…”
Section: Spontaneous Resolution and Preferential Crystallizationmentioning
confidence: 99%